2017
DOI: 10.1007/s00213-017-4772-9
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol increases inattentional blindness when cognitive resources are not consumed by ongoing task demands

Abstract: RationaleInattentional blindness (IB) is the inability to detect a salient yet unexpected task irrelevant stimulus in one’s visual field when attention is engaged in an ongoing primary task. The present study is the first to examine the impact of both task difficulty and alcohol consumption on IB and primary task performance.ObjectivesOn the basis of alcohol myopia theory, the combined effects of increased task difficulty and alcohol intoxication were predicted to impair task performance and restrict the focus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 29 publications
3
16
0
Order By: Relevance
“…Evidence that alcohol restricts attention to the processing of salient visual features is provided by a raft of basic cognitive experiments (e.g., Bayless & Harvey, ; Canto‐Pereira, David, Machado‐Pinheiro, & Ranvaud, ; Clifasefi, Takarangi, & Bergman, ; Harvey, ; Harvey, Bayless, & Hyams, ; Hoyer, Semenec, & Buchler, ; Moskowitz & Sharma, ; Schulte, Müller‐Oehring, Strasburger, Warzel, & Sabel, ) and a small but growing number of applied studies on alcohol and mock‐witness recall (for reviews see Altman et al, ; Jores et al, ). For example, Harvey et al () tracked the eye movements of sober and alcohol (M BAC = 0.06%) participants as they viewed two successive stimulus photographs each depicting a salient real‐world scene as its focus (e.g., riot police apprehending civilians with batons).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence that alcohol restricts attention to the processing of salient visual features is provided by a raft of basic cognitive experiments (e.g., Bayless & Harvey, ; Canto‐Pereira, David, Machado‐Pinheiro, & Ranvaud, ; Clifasefi, Takarangi, & Bergman, ; Harvey, ; Harvey, Bayless, & Hyams, ; Hoyer, Semenec, & Buchler, ; Moskowitz & Sharma, ; Schulte, Müller‐Oehring, Strasburger, Warzel, & Sabel, ) and a small but growing number of applied studies on alcohol and mock‐witness recall (for reviews see Altman et al, ; Jores et al, ). For example, Harvey et al () tracked the eye movements of sober and alcohol (M BAC = 0.06%) participants as they viewed two successive stimulus photographs each depicting a salient real‐world scene as its focus (e.g., riot police apprehending civilians with batons).…”
Section: Introductionmentioning
confidence: 99%
“…The theory of alcohol myopia has received support from varied laboratory studies of attention. It has been demonstrated that alcohol reduces distraction by stimuli that are competing for attention, ostensibly because attentional capacity is so reduced that there is no attentional reserve remaining to attend to stimuli that are not directly related to the primary task at hand (Erblich and Earleywine 1995;Jääskeläinen et al 1999;Clifasefi et al 2006;Allen et al 2009;Harvey et al 2018; see for reviews: Koelega 1995;Mocaiber et al 2011). For example, Erblich and Earlywine (1995) had participants perform tests of short-term memory both when intoxicated and when sober.…”
Section: Introductionmentioning
confidence: 99%
“…Only when participants were sober was memory performance impaired by verbal auditory distraction. Using the famous 'gorilla task' two studies reported increased inattentional blindness following alcohol administration, such that intoxicated participants who were asked to count the number of passes made between basketball players were less likely to notice a person dressed as a gorilla saunter across the basketball court than were those who were sober (Clifasefi et al 2006;Harvey et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Present in all alcoholic beverages, ethanol reaches the blood vessel system through normal digestion. Recognized as a toxin, ethanol is destroyed by the body; mainly in the liver, as it filters blood [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%